Object numerosity influence sensorimotor programs evoked by graspable object nouns - Garofalo, Gioacchino; Gherri, Elena; Lugli, Luisa; Prpic, Valter (Frontiers in Psychology, 2026)
Grasping actions can be evoked and modulated by a range of linguistic and abstract concepts, including object nouns, adjectives and numbers. The present study investigated whether the grasp-compatibility effect—typically elicited by graspable object nouns - is sensible to variations in numerosity. In Experiment 1, we tested graspable object nouns presented in the singular vs. plural form. In Experiment 2, we enhanced the salience of numerosity by adding quantifiers (one vs. many) to the same nouns. We hypothesized that object numerosity would be encoded alongside object size, thereby modulating the grasp-compatibility effect. Specifically, we expected that single object nouns, which are compatible with specific grasping actions, elicited a grasp-compatibility effect. Such effect should no longer be elicited when multiple objects are evoked (e.g., one apple is compatible with a power grasp., whereas many apples is no longer compatible with the same grasping action). The results indicate that the grasp-compatibility effect is not modulated by grammatical numbers alone (Experiment 1), but it disappears when numerosity is made explicit through the quantifier “many” (Experiment 2). These findings suggest that object numerosity can influence the sensorimotor simulation elicited by graspable object nouns, but only when numerosity is explicitly conveyed through semantic quantification rather than grammatical morphology.